2015
DOI: 10.1103/physrevb.92.144416
|View full text |Cite
|
Sign up to set email alerts
|

Spin-flop transition and magnetic phase diagram inCaCo2As2revealed by torque measurements

Abstract: The magnetic properties of CaCo2As2 single crystal was systematically studied by using dc magnetization and magnetic torque measurements. A paramagnetic to antiferromagnetic transition occurs at TN = 74 K with Co spins being aligned parallel to the c axis. For H c, a field-induced spin-flop transition was observed below TN and a magnetic transition from antiferromagnetic to paramagnetic was inferred from the detailed analysis of magnetization and magnetic torque. Finally, we summarize the magnetic phase diagra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
5
21
1
Order By: Relevance
“…Electronic structure calculations are consistent with the itinerant A-type AFM ground state and the small ordered moment [29]. Spin-flop transitions in single crystals of CaCo 2−y As 2 with the magnetic field H applied parallel to the c axis occur at H SF ∼ 3.5-3.7 T [25,26,30,31]. On the other hand, metallic SrCo 2 As 2 exhibits no magnetic transitions versus T [32].…”
supporting
confidence: 57%
“…Electronic structure calculations are consistent with the itinerant A-type AFM ground state and the small ordered moment [29]. Spin-flop transitions in single crystals of CaCo 2−y As 2 with the magnetic field H applied parallel to the c axis occur at H SF ∼ 3.5-3.7 T [25,26,30,31]. On the other hand, metallic SrCo 2 As 2 exhibits no magnetic transitions versus T [32].…”
supporting
confidence: 57%
“…Samples with Co vacancies seem to have lower values for T N , with T N = 52(1) K for y = 0.14 [17] and T N = 76 K for y = 0 [28]. On the other hand, it has been suggested that vacancies alone may not explain the differing values of T N from different reports and that different growth conditions may also be responsible [30].…”
Section: Resultsmentioning
confidence: 95%
“…What differentiates the B-T phase diagram of (NH 4 ) 2 FeCl 5 ⋅H 2 O from that of other molecule-based multiferroics is the exceptional level of detail. For instance, in metal-organic framework compounds such as (CH 3 ) 2 NH 2 ]Mn(HCOO) 3 , the phase diagram exhibits a spin flop near 0.3 T, a broad canted phase, and a transition to the fully saturated state at 15.3 T. 22 Likewise, in CaCo 2 As 2 , the critical fields are 3.7 and 7.5 T. 46 The overall simplicity of these B-T phase diagrams arises from the superexchange pathways through formate ligands or Co⋯As interactions, respectively. Magnetic exchange, of course, can also take place through hydrogen and halide bonds.…”
Section: Resultsmentioning
confidence: 99%